Granulomatosis with polyangiitis: Common and uncommon presentations. Issue 8 (20th September 2022) - Tee, Qiao Xin; Wong, Aaron; Nambiar, Mithun; Lau, Kenneth K
Summary: Granulomatosis with polyangiitis (GPA) is a multisystemic autoimmune small vessel vasculitis predominantly affecting the respiratory and renal systems. Other systems such as the central nervous system, orbital, cardiac and gastrointestinal systems may also be involved to a lesser degree. Although there are no imaging features that are pathognomonic for GPA, there are known radiological patterns suggestive of the disease and imaging plays an important role in diagnosis, assessment and monitoring of disease activity. This is more evident when combined with clinical features, biochemical values and histopathology results. This pictorial review aims to present both common and uncommon radiological features of GPA.